Leisure, Culture and Lifestyle - Veal, Anthony. (Loisir et Société / Society and Leisure)

(untitled) (Presses de l’Université du Québec, 2001)
AbstractThis paper examines the place of the concept of lifestyle in leisure studies in the light of three recent publications. In Leisure and Contemporary Society Ken Roberts (1999) concludes that lifestyle is not a key concept for leisure studies because it has not replaced factors such as age, gender and social class in providing individuals with a sense of identity. In Leisure and Culture, Chris Rojek (2000) reviews the distinctive features of the dominant theoretical paradigms of leisure studies/leisure sociology over the last thirty years, and suggests that, while cultural studies has had a major influence on leisure studies, in practice it has been preoccupied with class. He therefore suggests that a renewed focus on culture could provide a way forward for leisure studies/leisure sociology. Steven Miles (2000), in Youth Lifestyles in a Changing World, argues that the concept of subculture, traditionally used in studies of youth, has been compromised by its association with the structural, neo-Marxist paradigms of the cultural studies tradition of the 1980s and 1990s, and that therefore the term lifestyle is a more suitable concept for studying the lives of young people today. In the light of these and other recent contributions to leisure theory, the paper therefore argues that the concept of lifestyle remains a useful concept which can make a significant contribution to the development of leisure studies.